Comparison of fuzzy logic control and PI control for a three-level rectifier based on voltage oriented control - Ahmed, K.Y. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents a voltage oriented control (VOC) for a three level, three-phase PWM rectifier using a fuzzy logic control strategy. The PI control was replaced by fuzzy control aimed to reduce the total harmonic distortion (THD) on the grid side, to improve the power factor (PF) as well as keep the output DC voltage to the required level when a dynamic disturbance happens. The MATLAB/Simulink and fuzzy logic toolboxes have been used to investigate the steady-state and transient-state behaviors for the proposed controller. As the result shows, it was verified that the fuzzy logic controller is much better than the traditional PI controller, and the fuzzy logic controller provides a stellar performance in the transient state. © 2016 IEEE.